MAIN ASPECTS OF PROFESSIONAL LIABILITY INSURANCE FOR EXPERTS, LAWYERS AND ADVOCATES IN THE FEDERAL REPUBLIC OF GERMANY - Zaiets, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose professional liability insurance is an important component of risk management for professionals in various fields. This insurance protects professionals against claims arising from negligence, errors or omissions in the performance of their duties. In Germany, this type of insurance is mandatory for lawyers, attorneys and experts, due to the nature of their work, which often involves significant legal and financial liability. Research methods: the study is based on general scientific methods as well as specific legal methods, with the help of which various scientific positions and doctrinal approaches to the development of ideas regarding understanding the concept and essence of legal fictions, as well as their significance in legal sphere, have been analyzed. Results: we will look at the specifics of professional liability insurance for experts, attorneys and advocates in Germany. This includes the legislative framework, the role of insurance in professional practice and the specific rules that apply to these professions. Discussion: professional liability insurance is an important guarantee for lawyers, attorneys and experts in Germany. The Federal Lawyers Act (BRAO) and the Professional Code of Conduct for Lawyers (BORA) provide for mandatory liability insurance for practicing lawyers, guaranteeing their financial protection against claims caused by negligence or errors. The German Civil Code (BGB) further clarifies the principles of liability, providing a legal basis for claims. Industry regulations ensure that experts also have insurance to protect their clients. For lawyers and experts, professional liability insurance is not just a legal obligation; it is an obligation to their clients, ensuring that they can trust the advice and actions of the professional. By adhering to legal and ethical requirements, these professionals reduce the financial risks of abuse and ensure the integrity of their services.